2019
DOI: 10.1038/s41598-019-39980-y
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Viremia, Cloacal Virus Shedding, Antibody Responses and Pathological Lesions in Adult Chickens, Quails, and Pigeons Infected with ALV-A

Abstract: Subgroup A of the avian leukosis virus (ALV-A) can cause severe pathological lesions and death in infected chickens, and its reported hosts have increased recently. To assess the susceptibility of adult chickens, quails, and pigeons to ALV-A, three sets of 250-day-old birds were intraperitoneally inoculated with ALV-A. Viremia and cloacal virus shedding were dynamically detected using an immunofluorescence assay (IFA), ALV-P27 antigen ELISA or RT-PCR; pathological lesions were assessed using tissue sections; A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 21 publications
0
17
0
Order By: Relevance
“…Japanese quail ( Coturnix japonica ) have become the focus of many biological studies because of their relatively small size, fast sexual maturation, and abundant egg production ( Huss et al., 2008 ; Seidl et al., 2013 ; Choi et al., 2014 ; Shin et al., 2015 ). In addition, Japanese quail have been used as an animal model for studying susceptibility, transmission, and pathogenesis of various avian viruses and are highly susceptible to influenza A viruses ( IAV ) and many other viruses including Newcastle disease virus and avian leucosis virus ( Thontiravong et al., 2012 ; Sharawi et al., 2015 ; Susta et al., 2018 ; Zhang et al., 2019 ). Thus, quail can serve as a great avian transgenesis model to study gene functions in relation to viral pathogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Japanese quail ( Coturnix japonica ) have become the focus of many biological studies because of their relatively small size, fast sexual maturation, and abundant egg production ( Huss et al., 2008 ; Seidl et al., 2013 ; Choi et al., 2014 ; Shin et al., 2015 ). In addition, Japanese quail have been used as an animal model for studying susceptibility, transmission, and pathogenesis of various avian viruses and are highly susceptible to influenza A viruses ( IAV ) and many other viruses including Newcastle disease virus and avian leucosis virus ( Thontiravong et al., 2012 ; Sharawi et al., 2015 ; Susta et al., 2018 ; Zhang et al., 2019 ). Thus, quail can serve as a great avian transgenesis model to study gene functions in relation to viral pathogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…ALV, an oncogenic retrovirus, can cause immunosuppression, decreased production performance, tumours and even death in chickens [20][21][22][23]. ALV is divided into 11 subgroups from A to K according to the host range, antibody neutralization and receptor interference studies, and seven of these subgroups, namely, ALV-A/ B/C/D/E/J/K, can infect chickens [24][25][26][27].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, DF1 cells were inoculated with the ALV-A-SDAU09C1 strain, which was isolated from imported ancestral breeding broiler chickens in 2009 [ 19 ] and was reported to replicate in DF1 cells and to be pathogenic in chickens [ 19 , 20 , 37 ]. The expression of chicken TRIM25 at both the mRNA and protein levels was significantly increased, which suggests that the antiviral responses mediated by TRIM25 were induced.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Avian Leukosis Virus (ALV) could induce tumors in Japanese quails (Wight, 1963) and quails with lymphoproliferative disease had antibodies against ALV subgroup A (Schat et al, 1976). Recently, it was observed that intraperitoneal inoculation of quails with ALV subgroup A induced transient viremia, intermittent cloacal shedding and mild lesions in infected quails (Zhang et al, 2019). Quails are susceptible to experimental infection with reticuloendotheliosis virus (Theilen et al, 1966).…”
Section: Tumorsmentioning
confidence: 99%